Appendicitis Clinical Pathway Implementations Compliance Evaluation in Hospital - Wijaya, Adi Indra; Dewi, Arlina; Listiowati, Ekorini (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Clinical pathway (CP) is a collaborative guidance for patients treatments that focused on diagnosis, clinical problems, and stages of care. CP implementation becomes a guideline on hospital quality and safety improvement for the patient services. Method: The research used a descriptive-qualitative mixed methods. Primary data collected through medical record and secondary data is done by interview and observation by using CP format. Results: From medical records total, 23 cases were found that met the inclusion criteria. The acute appendicitis case in adults is more than children in number (3,6:1). Acute appendicitis CP compliance is 86%. There are three problems in CP compliance of acute appendicitis i.e doctor's visit adherence (physician in charge of patient 87%, 0% anesthesia), 65% adherence therapy compliance, and 52% inpatient admission. The root of the problem is the lack of socialization, monitoring, and evaluation of established standards. Some activity variations may occur during each process from time to time that will produce a variety of the outcomes as well. How to reduce process variation is to standardize. The process of standardization includes the preparation, socialization, monitoring, control, evaluation and revision of thew standards. CP profit is that it could reduce variation, is a professional requirement, and the basis for quality measurement. Implementation of good standards will ensure the safety of patients and the healthcare providers. Conclusion: Almost all employees have conducted medical record (MR) in accordance with clinical pathway criteria as well, but the CP sheet is not included in the MR